The Role of AI in Content Creation: A Case Study of Mwananchi Communications Limited (MCL) and Tanzania Standard Newspapers - Mlwilo, Geofrey J.; Britto, Rejandran; Nikata, Camillus (Journal of Media, Journalism & Mass Communication, 2026)
This study examines the adoption of Artificial Intelligence (AI) in Tanzanian newsrooms, focusing on Mwananchi Communications Limited (MCL) and Tanzania Standard Newspapers (TSN). Despite global interest in AI for journalism, limited research addresses its use in African contexts, where training and resources are often constrained. A qualitative case study approach was employed, using interviews and observations with journalists and digital media staff. Findings indicate that AI tools such as ChatGPT, Grammarly, Piktochart, Canva, Google Analytics, and Transkriptor support drafting, transcription, data visualization, and audience analysis, but adoption is uneven, with 50% engagement on the Online/Digital Desk compared to 20% on the Print Desk. Key challenges include limited formal training (95% of journalists untrained), inadequate infrastructure, and absence of editorial policies or ethical guidelines. The study highlights AI’s potential to improve efficiency and workflows while emphasizing the need for structured training, policy frameworks, and transparency to ensure responsible adoption, safeguard journalistic integrity, and enhance content quality in Tanzania.